Republic of Poland : Financial Sector Assessment Program-Technical Note-Cooperative Banks and Credit Unions. (IMF Staff Country Reports; Country Report, 2019)
This Technical Note on Cooperative Banks and Credit Unions for the Republic of Poland reviews the cooperative bank and credit union sectors. It focuses on: the situation of the two sectors that are both in states of transition; the regulatory and supervisory arrangements; and the safety net and resolution regime within the context of the crisis management framework. In addition, key perspectives are provided as to the sustainability of institutional models and the sectors within a modernizing and competitive banking sector. Most cooperative banks and credit unions are found to be stable; however, each sector has its own issues. The Financial Sector Assessment Program is broadly supportive of the policy direction for cooperatives, while it questions whether the credit union sector should remain standalone. The two existing Institutional Protection Schemes and their affiliating banks need to be strengthened to ensure sustainability. Policymakers are thus advised to decide whether a standalone credit union sector remains appropriate and, if not, define a strategy to transition viable credit unions to become or consolidate with banks.